Promising Technologies for Small-Scale Farmers: Overcoming Challenges - Abousabaa, Aly (2018)
The IFPRI-Egypt Seminar Series is part of the United States Agency for International Development (USAID) funded project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI. The seminar supports USAID’s Agribusiness for Rural Development and Increasing Incomes (ARDII) project’s objectives.